Development Approach of Marinade Powder from Suaeda maritima for Fish - Tongkam, Saichon; Chokumnoyporn, Napapan; Chum-in, Thinnaphop (Journal of Applied Research on Science and Technology (JARST), 2022)
This research aims to study and find a guideline for the development of fish seasoning and marinade powder from Suaeda maritima. seasoning powder from Suaeda maritima for marinating fish. The study was divided into 4 approaches: (1) focus group discussion, (2) questionnaire, (3) raw materials quality analysis of dried Suaeda maritima and (4) preliminary acceptance assessment of fish marinating. Results from focus group discussions and questionnaires illustrated that used as the guidelines for the development of fish seasoning and marinade powder from Suaeda maritima showed that product should have the natural flavor from herbal ingredients, antioxidants and salt content reduction. It should not have contained monosodium glutamate. This product should be packed in zip lock bags and glass bottles. The amount for this product ranged from 70-100 g/1 package. The quality analysis of raw materials from the drying process, found that dried Suaeda maritima contained sodium content 8,680.50 mg /100 g and the antioxidant capacity (Trolox) 1,307.23 (mg eq Trolox/100 g). In addition, the result of consumer acceptance for different fish marinating formulation showed that consumers accepted fish using marinating with Suaeda maritima powder at like slightly to like moderately in all quality attributes: color, odor, taste, texture and overall- preference with the preference scores between 6.1-7.6. Thus, it is possible to further research for using dried Suaeda maritima powder to be applied as the main ingredient of seasoning powder for marinating fish.